Traditional Kaingin (Deforestation) Practices: The Case of Daraitan Dumagats - Ibanez, Jeruel B.; Canesares, Cutie B.; Aclan, Eunice M.; Acquioben, Edmund R. (11th International Scholars Conference, 2018)
Many indigenous groups in the Philippines, especially those living in the mountainous regions, continue to practice the traditional deforestation called kaingin. Kaingin is slashing and burning of trees and plowing the ashes for fertilizer. It causes soil erosion, loss of soil fertility, and climate change. It is an illegal farming practice, which the Dumagats of Daraitan, Tanay, Rizal are aware of. However, they do not have any alternative way of farming. This paper, based on Ogburn’s Social Change Theory, is a qualitative case study that aimed to understand the cultural meaning of kaingin to the Dumagats and why they continue to practice it despite the environmental laws in the country. Also, this study proposes an alternative upland farming for environmental and economic sustainability. Data thematically analyzed were from the focus group discussions (FGD) and one-on-one interviews with the tribal kaingenyeros. Results showed that kaingin is a part of Dumagat culture and it is a source of their social and economic (socio-economic) bonding and therefore, cultural preservation. Furthermore, despite law’s prohibition, they continue the practice because they have no alternative land to till except the mountains which are their ancestral lands. They also lack education and training in farming. Alley cropping is proposed to restore the soil fertility without destroying the cultural economic bonding of the Dumagats by growing suitable plants based on the soil type as farm alleys while planting other crops such as corn in between the alleys without using chemicals as the leaves of the alley plants may serve as organic fertilizer.